Pertussis outbreak in Polish shooters with adverse event analysis - Skrzypiec-Spring, Monika; Krzywański, Jarosław; Karlikowska-Skwarnik, Monika; Pokrywka, Andrzej; Krysztofiak, Hubert; Nitsch-Osuch, Aneta; Kuchar, Ernest (Biology of Sport, 2017)
In addition to different injuries, infections are the most common reason for giving up training altogether or reducing its volume and intensity, as well as a lack of opportunities to participate in sports competitions. Nowadays, a slow but constant re‑emergence of pertussis, especially among teenagers and young adults, including athletes, can be observed. This paper describes an outbreak of pertussis among professional Polish shooters, focusing on the transmission of Bordetella pertussis infection between members of the national team, its influence on performance capacity and adverse event analysis. From 9 June, 2015 to 31 July, 2015, a total of 4 confirmed and suspected cases of pertussis were reported among members of the Polish Sport Shooting National Team, their relatives and acquaintances. Pertussis significantly decreased exercise performance of the first athlete, a 35-year-old woman, interrupted her training, and finally resulted in failure to win a medal or quota place. Pertussis also significantly decreased performance of the second athlete, a 25-year-old shooter. The other cases emerged in their families. Whooping cough is a real threat to athletes and should be prevented. Preventive measures include appropriate immunization, constant medical supervision, as well as early isolation, diagnostic tests and treatment of all infected sport team members. Regular administration of booster doses of the acellular pertussis vaccine (Tdpa) every 5 years seems reasonable.